The relationship of chemokine levels and the type of symptoms caused by NSAIDs or alcohol in patients with NSAIDs-exacerbated respiratory disease - Frachowicz-Guerreiro, Karolina; Gajewski, Adrian; Chałubiński, Maciej; Wardzyńska, Aleksandra (Frontiers in Immunology, 2026)
IntroductionNonsteroidal anti-inflammatory drug (NSAID)-exacerbated respiratory disease (N-ERD) is an asthma phenotype with a complex pathogenesis involving chemokine-mediated inflammation. This study aimed to evaluate the association between chemokine levels and symptoms triggered by NSAIDs and alcohol in patients with N-ERD.MethodsSeventy-two subjects (41 N-ERD, 20 NSAID-tolerant asthma [NTA], and 11 healthy controls) were assessed via questionnaire, lung function tests, and measurement of selected chemokines in serum, urine, and exhaled breath condensate (EBC).ResultsN-ERD patients exhibited significantly higher CCL17/TARC levels in EBC compared to controls (p<0.001). Both N-ERD and NTA groups had elevated serum CCL5/RANTES levels relative to controls (p=0.002 and p=0.04, respectively). Respiratory symptoms after alcohol consumption were reported by 48% of N-ERD patients, significantly more frequent than in controls (p<0.05), with dyspnea more common in N-ERD than NTA (p=0.03). In N-ERD patients, serum CCL17/TARC levels were lower in those experiencing dyspnea after NSAIDs (p=0.03), while serum CXCL10/IP-10 levels were higher in patients with mixed (not only respiratory) symptoms (p=0.015). Alcohol symptoms in N-ERD correlated with lower urinary CCL5/RANTES levels (p=0.01). Nasal blockage after alcohol was associated with reduced CCL17/TARC in EBC (p=0.01), and dyspnea after alcohol correlated with lower serum CCL26/Eotaxin-3 (p=0.047).ConclusionChemokine profiles differ according to symptom type following NSAID or alcohol exposure in N-ERD patients. These findings highlight the heterogeneity of N-ERD and suggest distinct inflammatory pathways linked to clinical presentations.